Medication dispenser with touch screen and consumption authenticator for monitoring adherence to medication in the elderly - Linder Rubiños Jimenez, Santiago; Adolfo Vidal Sánchez, Ricardo Sergio; Enrique Solis Farfán, Roberto; Alfredo Vallejos Zuta, Alex; Junior Grados Espinoza, Herbert; Linett Velasquez Jimenez, Angélica (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The elderly population continues to grow, this population has many chronic conditions, which is why they take multiple pills at the same time, this situation makes it difficult for them to take their medications at the appropriate time, which can cause health complications and even death. death. The objective of this research is to improve medication adherence using a medication dispenser that allows authenticating medication consumption accurately with a high level of usability. To do this, we implemented a dispenser with an alarm system that can be configured from a graphical interface, with internet of things (IoT) to remotely monitor the intake of pills and authenticate their consumption through artificial vision that will use the instant messaging system to inform the caregiver about the situation and finally measure the dispenser usability.